Green approaches and barriers of green hotels and resorts in Peninsular Malaysia - Yusof, Zeenat Begam; Sapian, Abdul Razak (2014)
Tourism is one of the biggest industries in the world. It is growing faster than other notable industries in the world such as manufacturing, retail and financial industry. Tourism industry provides direct contribution to the world economy. Even though this industry does not directly pollute the environment, its cumulative negative impacts on the environment are notable. This industry is a resource consumptive industry. It consumes water and energy and produce various waste such as solid and liquid waste. The negative impacts of this industry are numerous. The impacts are directly and indirectly on the environment. This study is focusing on the direct negative caused by tourism industry on the natural environment. Resorts and hotels are some example of the tourism accommodation component. Hotels and resort operation consumes a lot of resources and produce a lot of waste and emission. Consequently, it is vital for the resorts and hotel operator to adopt some green approaches in their operation in order to reduce their operational negative impacts. Currently there are only 12 green resorts and hotels, which are recognized in Malaysia. Studies have shown that there are limited numbers of studies are conducted regarding the green approaches of green hotels and resorts in Malaysia. Therefore, this study is conducted to fulfill the gap in the literature. The main aim of this research is to identify the green approaches and barriers of green resorts and hotels in Malaysia. There are two objectives of this research. The first objective is to determine the area of green approaches and the rate of participation of Malaysia green operators. The second objective is to determine the barriers faced by Malaysian green operators. The research techniques adopted for this study are in-depth interviews, structure observations and document analysis. Five resorts and hotels were selected as case studies. ASEAN Tourism Standard (ATS) awarded all the case studies as green hotels and resorts in 2012 until 2014. The finding shows that the areas with the greenest participation are in the area of energy, waste and water because these areas reduce operational cost. The areas of less participation are in the indoor air quality and sustainable site management because these of the areas have less impact on the operational costs. Participation in new technology areas such as renewable energy (solar panel) and a rainwater harvesting system is also less due to the higher cost and system availability. The findings also show that different operators have adopted different green approaches in the operations. The reasons are the management policy, cost, availability, surrounding context and land size. Three types of barriers were identified in this study. The barriers were identified are significant barriers, less-significant barriers and non-significant barriers. The non-significant barriers are the barriers that did not affect to become green operators. Where else significant barriers mean that the barriers that affect to become green operators. The example of significant barriers is a lack of green experts, lack of resources in-term of manpower, green equipment and difficulty in balancing the quality of service with environmental performance. Whereas, the example of less-significant barriers is high implementation cost, high maintenance cost and lack of government support. The example of non-significant barriers is lack of green information and knowledge, uncertainty of green outcome, lack of support from the owner and management, lack of consumer supports and lack of green supplier networking. Finally, the study has shown that the green operators only need to confront several barriers to become a green operator in Malaysia. This is due to the good support from the parent company and guests, no uncertainty of green business, have adequate green knowledge and have good supplier contact. This study also has identified the several common green approaches of the green operators in Malaysia. The findings of this study, add a knowledge or gap in the existing field of green approaches to literature. The limitation of the study is small numbers of case studies, which required further studies to be conducted in future. In conclusion, this study did answer the research questions and had achieved the objectives.